Rekonstruksi Dimensi Transendental dan Sosial Generasi “Z” Masyarakat Gunung Kemukus Sragen Pasca Penutupan Lokalisasi - Muhammad Miftah (Jurnal Penelitian, 2018)
Mindset is formed from the pattern of interaction among the individualswhose habit and daily behavior,then it is always repeatedso it becomes a character. The leverage level of generation Z mindset is still very vulnerable because they are influenced by environment and technological developments. They are literate and always interact with technology in life activities. The environmental urge and patterns of interaction within a community in various researches play the most vital role in human behavior change. This theory is used as the foundation of the writer to conduct research in the area of Mount Kemukus which has become a place of ritual "lokalisasi" that impersonate religion for many years.This condition gets big attention from local governments and world. However, the stigma began to erode through government policy toclose those places and save Mount Kemukus from immoral practices. This research will focus on examining how the local government's education policy reconstructs the generation Z mindset without excluding the ancestral culture (local wisdom) as the regional distinction compared to other regions. The government policy in reconstructing the millennial mindset can be seen from policies in social, educational, economic and religious dimensions.